Nimesulide-induced fatal acute liver failure in an elderly woman with metastatic biliary adenocarcinoma: a case report - Bernardes, Sara Santos; Souza-Nogueira, André; Moreira, Estefânia Gastaldello; Kishima, Marina Okuyama; Guembarovski, Alda Fiorina Maria Losi; Turini, Tercilio Luiz; Turini, Conceição Aparecida (São Paulo Medical Journal, 2015)
CONTEXT: Nimesulide is a selective inhibitor of the enzyme cyclooxygenase 2. Although considered to be a safe drug, cases of acute hepatitis and fulminant liver failure have been reported in Europe, the United States and South America, especially among elderly female patients. Until now, there had not been any reports in the literature relating to Brazilian subjects. CASE REPORT: An 81-year old female who had been using nimesulide therapy for six days presented hematemesis and epistaxis two days before hospitalization. Clinical examination showed an extensive coagulation disorder, diffuse hematomas, hypotension and tachypnea. Laboratory tests revealed abnor-malities in coagulation tests; leukocytosis; reduced platelet, hemoglobin and red blood cell counts; and elevated direct bilirubin, serum aspartate transaminase (AST), gamma-glutamyl transpeptidase (GGT), alkaline phosphatase and renal function biomarkers. Hepatitis B and C tests were not reactive. Carcino-embryonic antigen (CEA), CA-19-9 and CA-125 levels were increased by, respectively, 1,000, 10,000 and 13 fold, whereas the alpha-fetoprotein level was normal, thus indicating a malignant tumor in the bile duct that did not originate from the liver. Thirty-six hours after hospitalization, the patient’s condition worsened, leading to death. The necropsy findings included acute hepatitis with hepatocellular collapse, as well as metastasis of a carcinoma, probably from the bile duct. CONCLUSION: Despite the carcinoma presented by the patient, nimesulide use may have contributed towards the fatal acute liver failure. Until this issue has been clarified, caution is required in prescribing nimesulide for liver disease patients.